Le MT180® ou les infortunes de l'excellence - Jean Frances; Stéphane Le Lay
Ten years ago, My Thesis in 180 Seconds ® (MT180®) appeared in the world Francophone higher education. Modelled on Australia's Three Minute Thesis (3MT), this communication competition for doctoral students engages students in a public speaking competition in which they have three minutes to pitch their research projects. In this sense, MT180 might be understood as a sort of popularization contest aiming to shed light on the "research report." Yet when one considers what is in play more closely (Corsi et al), this interpretation becomes questionable. Indeed, once one begins to ask former participants about their opinions regarding their experiences over the course of the competition, the idea that My Thesis primarily serves to bring science out of the laboratory and to raise interest in researchers becomes ever more clearly in need of being re-examined. This rethinking of what is at stake in MT180 is what we present here.